2014
DOI: 10.1073/pnas.1402351111
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of hepcidin and iron regulation during HIV-1, HBV, and HCV infections

Abstract: Significance Altered iron levels correlate with disease progression in HIV type-1 (HIV-1) infection, and cellular iron promotes HIV-1 replication. In chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infections, increased liver iron levels contribute to disease. The peptide hormone hepcidin controls iron distribution. We find that hepcidin increases during the acute phase of HIV-1 infection, early hepcidin predicts later plasma viral set-point, and hepcidin remains high even in chronically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 46 publications
3
103
0
Order By: Relevance
“…Altered hepcidin expression has been described in hepatitis B and hepatitis C infection, 43,44 but observations of changes in hepcidin levels in HIV infection are conflicting. Hepcidin levels were shown to be increased in HIV infection with or without ART, which is consistent with reduced serum iron levels, 45 but another study demonstrated reduced hepcidin levels in HIV-positive women, which can lead to increased iron release into the circulation. 46 Our results are more consistent with reduced hepcidin levels leading to increased serum iron, although we did not measure hepcidin levels in our studies.…”
Section: Relationship Among Iron Hiv and Art 309mentioning
confidence: 77%
“…Altered hepcidin expression has been described in hepatitis B and hepatitis C infection, 43,44 but observations of changes in hepcidin levels in HIV infection are conflicting. Hepcidin levels were shown to be increased in HIV infection with or without ART, which is consistent with reduced serum iron levels, 45 but another study demonstrated reduced hepcidin levels in HIV-positive women, which can lead to increased iron release into the circulation. 46 Our results are more consistent with reduced hepcidin levels leading to increased serum iron, although we did not measure hepcidin levels in our studies.…”
Section: Relationship Among Iron Hiv and Art 309mentioning
confidence: 77%
“…Interestingly, although most bacterial and some viral infections (such as influenza virus and HIV) rapidly increase hepcidin production in humans and mouse models, hepatitis B and hepatitis C virus infections fail to elicit systemic inflammatory responses and hepcidin production 30 . The consequences of the altered inflammatory and iron responses for infections with these liver-tropic viruses remain to be determined.…”
Section: Hepcidin and Host Defencementioning
confidence: 99%
“…For example, while many infections upregulate hepcidin and induce hypoferremia, hepatits B and hepatitis C viruses do not elicit a systemic inflammatory response or induce hepcidin or hypoferremia [36]. …”
Section: Hepcidin and The Pathogenesis Of Aimentioning
confidence: 99%